The MHC-II transactivator CIITA, a restriction factor against oncogenic HTLV-1 and HTLV-2 retroviruses: similarities and differences in the inhibition of Tax-1 and Tax-2 viral transactivators - Forlani, Greta; Abdallah, Rawan; Accolla, Roberto S.; Tosi, Giovanna (Frontiers in Microbiology, 2013)
The activation of CD4+ T helper cells is strictly dependent on the presentation of antigenic peptides by MHC Class II molecules. MHC-II expression is primarily regulated at the transcriptional level by the AIR-1 gene product CIITA (Class II transactivator). Thus, CIITA plays a pivotal role in the triggering of the adaptive immune response against pathogens. Beside this well known function, we recently found that CIITA acts as an endogenous restriction factor against HTLV-1 and HTLV-2 oncogenic retroviruses by targeting their viral transactivators Tax-1 and Tax-2, respectively. Here we review our findings on CIITA-mediated inhibition of viral replication and discuss similarities and differences in the molecular mechanisms by which CIITA specifically counteracts the function of Tax-1 and Tax-2 molecules. The dual function of CIITA as a key regulator of adaptive and intrinsic immunity represents a rather unique example of adaptation of host-derived factors against pathogen infections during evolution.